Regulation of plasmalogen metabolism and traffic in mammals: The fog begins to lift - Dorninger, Fabian; Werner, Ernst R.; Berger, Johannes; Watschinger, Katrin (Frontiers in Cell and Developmental Biology, 2022)
Due to their unique chemical structure, plasmalogens do not only exhibit distinct biophysical and biochemical features, but require specialized pathways of biosynthesis and metabolization. Recently, major advances have been made in our understanding of these processes, for example by the attribution of the gene encoding the enzyme, which catalyzes the final desaturation step in plasmalogen biosynthesis, or by the identification of cytochrome C as plasmalogenase, which allows for the degradation of plasmalogens. Also, models have been presented that plausibly explain the maintenance of adequate cellular levels of plasmalogens. However, despite the progress, many aspects around the questions of how plasmalogen metabolism is regulated and how plasmalogens are distributed among organs and tissues in more complex organisms like mammals, remain unresolved. Here, we summarize and interpret current evidence on the regulation of the enzymes involved in plasmalogen biosynthesis and degradation as well as the turnover of plasmalogens. Finally, we focus on plasmalogen traffic across the mammalian body – a topic of major importance, when considering plasmalogen replacement therapies in human disorders, where deficiencies in these lipids have been reported. These involve not only inborn errors in plasmalogen metabolism, but also more common diseases including Alzheimer’s disease and neurodevelopmental disorders.